Can common stocks provide a hedge against inflation? Evidence from African countries - Paul Alagidede; Theodore Panagiotidis (TÜSİAD-Koç University Economic Research Forum, 2010)
The extent to which the stock market provides a hedge to investors against inflation is examined for African stock markets. By employing parametric and nonparametric cointegration procedures, we show that the point estimates of the elasticities of stock prices with respect to consumer prices range from 0.015 for Tunisia to 2.264 for South Africa, evidence of a positive long-run relationship. Further, the time path of the response of stock prices to innovations in consumer prices exhibits a transitory negative response for Egypt and South Africa, which becomes positive over longer horizons: important indication that the stock market tends to provide a hedge against rising consumer prices in African markets.
Keywords: G10; G15; C32; 330; Stock Prices; Inflation; Fisher Effect; African Stock Markets; Cointegration; Börsenkurs; Aktie; Inflation; Kointegration; Fisher-Effekt; Afrika